Impact of rapid antibiotic susceptibility testing for Gram-negative bacteremia varies by pathogen type and resistance: a secondary analysis of the RAPIDS GN trial - Ritu Banerjee; Abhigya Giri; Lauren Komarow; Maria Souli; Sarah B. Doernberg; Robin Patel (Microbiology Spectrum)
ABSTRACT In this secondary analysis of 386 subjects with Gram-negative bacteremia enrolled in the RAPIDS GN trial, rapid antibiotic susceptibility testing had a greater benefit on the management of bacteremia caused by antibiotic-resistant compared to antibiotic-susceptible isolates, especially for Escherichia coli, Klebsiella species, and Proteus species.IMPORTANCERapid blood culture diagnostics are costly, and their use has not demonstrated clear clinical benefit for patients with Gram-negative sepsis, possibly because prior trials did not enroll sufficient numbers of patients with antibiotic-resistant infections. This analysis of patients with sepsis previously enrolled in a randomized controlled clinical trial demonstrates that rapid susceptibility testing of bacteria from blood cultures had the greatest impact for patients with antibiotic-resistant infections. Specifically, after rapid testing results were reported, patients infected with resistant bacteria received appropriate antibiotic therapy more quickly than patients with susceptible bacteria. These findings highlight the need to evaluate blood culture diagnostics in areas with high antibiotic resistance where these diagnostics are likely to have the greatest impact.